Analisis Parameter Dinamik Tanah pada Tanah Pasir yang Berpotensi Likuifaksi - Utari Sriwijaya Minaka; Ghina Amalia (Jurnal Tekno Global, 2022)
Shear modulus and damping ratio are two well-known dynamic properties of soil when subjected to cyclic loading. These values are influenced by several things, including groundwater level and soil stiffness. Since soil dynamic properties value varies by liquefaction, there is a need for laboratory research to specifically investigate the effect of degree of saturation and number of loads on shear modulus and damping ratio of sand. Cyclic Triaxial and Centrifuge tests were conducted to determine shear modulus and damping ratio under cyclic loading. For the Cyclic Triaxial test, Sekarsuli sand with 49,20% density, 50%, 75%, 100% degree of saturation, and two types of loading (10 and 20 cyclic) were used. Centrifuge test was conducted using 4 layers of Toyoura sand with 60% density, fully saturated, and two types of shaking (24 Hz and 30 Hz). The results revealed that shear modulus value increased as depth increased. The greater the number of cyclic applied, the shear modulus value increased, while the value of the damping ratio decreased. Centrifuge test also showed that, under fully saturated condition, the greater load applied, soil stiffness gradually decreased and shear strain increased. This resulted in the decrease in shear modulus and increase damping ratio value.